STUDENTS’ LEARNING AUTONOMY READINESS IN GRADE 9 OF ENGLISH SUBJECT IN INDONESIA - Jessica Nova Sagita; Bernard Wijaya Napitupulu; Dylmoon Hidayat (Universitas Sembilanbelas November Kolaka, 2022)
Education now requires students to be more active in the classroom because they are the center of learning. However, what often happens is that students show less initiative in learning. The level of learning autonomy readiness of grade 9 students in English lessons is measured in this study because they will advance to the high school level where the demand for autonomous learning is higher. The data population came from the 9th grade students of a private school in Indonesia. The data were collected through the Learner Autonomy Readiness questionnaire which was adapted from Chan et.al. (2002) on a scale of 1-5, to measure students' perceptions of responsibility, decision-making ability, motivation, and English learning activities, with a reliability level of 0.895 based on the Cronbach alpha coefficient. Data analysis was conducted using descriptive statistics and it was found that respondents tended to be less prepared (2,963 on a scale of 1-5) for autonomous learning in English lessons, especially in terms of their perception of their own responsibility in learning and independent learning activities in the classroom. To find factors that can support autonomous learning, further qualitative research is needed.